2003
DOI: 10.1089/104303403765701178
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Therapy Against Experimental Glioblastoma Using Genetically Engineered Cells Producing Interferon-α, Angiostatin, or Endostatin

Abstract: Inhibition of angiogenesis has been considered among the most promising approaches to treat highly vascularized solid tumors such as glioblastoma. In this study, we designed and validated a new in vitro assay system based on the implantation of tumor cells into organotypic brain slice cultures. We evaluated the effects of local production of three endogenous inhibitors of angiogenesis, angiostatin, endostatin, and interferon (IFN)-alpha(1), using stably transfected rat (9L) and human (GL15) glioblastoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…29 In addition, we used six fresh human specimens obtained from malignant glioma resection. After surgery, samples were immediately transferred to glioma-cell medium and prepared for implantation into brain slices obtained from young mice (see below).…”
Section: Cell Lines and Human Tumor Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In addition, we used six fresh human specimens obtained from malignant glioma resection. After surgery, samples were immediately transferred to glioma-cell medium and prepared for implantation into brain slices obtained from young mice (see below).…”
Section: Cell Lines and Human Tumor Samplesmentioning
confidence: 99%
“…Alternatively, this failure of anti-invasive effect may be due to a parallel increase in glioma invasion during antiangiogenic therapy. 29,42,43 Instead, it has been recently suggested that antiangiogenic therapy, which increases tumor hypoxia, may increase cell invasion by activating proinvasive signaling pathways. 44 The ability of sunitinib to exert antiangiogenic effects in an intracranial GBM model is a new and important finding.…”
mentioning
confidence: 99%
“…This activity has been mainly attributed to indirect effects, including inhibition of basic fibroblast growth factor production by tumor cells (5) or down-regulation of IL-8 and vascular endothelial growth factor gene expression (6,7). In contrast, other data indicate that IFN-␣ also has direct effects on endothelial cells (EC), 4 including impairment of EC proliferation and migration (3,4,8). In addition, IFN-␥ may exert antiangiogenic activity both directly through cytostatic effects on proliferating EC (9) and indirectly through the induction of angiostatic chemokine expression in vivo (10,11).…”
mentioning
confidence: 99%
“…Endogenous inhibitors such as interferon-α, angiostatin and endostatin were successfully formulated for use in brain tumor models. [59][60][61][62] Sengupta et al 63 developed a multi-drug delivery system composed of a copolymer PLGA and Phosphatidylcholine:cholesterol (PEG-DSPE) named nanocell, which enables the release of two drugs at different kinetics. The outer PEG-DSPE shell first releases an antiangiogenic agent, combretastatin, which regresses blood vessel growth, while the inner core of the nanoparticle composed of a polymer PLGA-doxorubicin, is trapped inside the tumor and slowly releases the chemotherapy drug.…”
Section: Drug Delivery Across the Blood-brain-barriermentioning
confidence: 99%